Dereplication by HPLC‐DAD‐ESI‐MS/MS and Screening for Biological Activities of Byrsonima Species (Malpighiaceae). Issue 2 (9th October 2017) - Fraige, Karina; Dametto, Alessandra Cristina; Zeraik, Maria Luiza; de Freitas, Larissa; Saraiva, Amanda Correia; Medeiros, Alexandra Ivo; Castro‐Gamboa, Ian; Cavalheiro, Alberto José; Silva, Dulce Helena S.; Lopes, Norberto Peporine; Bolzani, Vanderlan S.
Abstract: Introduction: Byrsonima species have been used in the treatment of gastrointestinal and gynecological inflammations, skin infections and snakebites. Based on their biological activities, it is important to study other organisms from this genus and to identify their metabolites. Objectives: To determine the metabolic fingerprinting of methanol and ethyl acetate extracts of four Byrsonima species ( B. intermedia, B. coccolobifolia, B. verbascifolia and B. sericea ) by HPLC‐DAD‐ESI‐MS/MS and evaluate their in vitro antioxidant, anti‐glycation, anti‐inflammatory and cytotoxic activities. Materials and methods: Antioxidant activity was determined by DPPH˙, ABTS˙ + and ROO˙ scavenging assays. Anti‐glycation activity was evaluated by the ability to inhibit the formation of advanced glycation endproducts (AGEs). Anti‐inflammatory activity was evaluated using a murine macrophage cell line (RAW 264–7) in the presence of lipopolysaccharide (LPS). Tumour necrosis factor alpha (TNF‐α) and nitrite (NO2 − ) production were measured by ELISA and the Griess reaction, respectively. The compounds present in the extracts were tentatively identified by HPLC‐DAD‐ESI‐MS/MS. Results: The evaluation of the biological activities showed the potential of the extracts. The activities were assigned to the presence of glycoside flavonoids mainly derived from quercetin, quinic acid derivatives, gallic acid derivatives, galloylquinic acids and proanthocyanidins. Two isomers of sinapic acid‐ O ‐hexoside were described for the first time in a Byrsonima species. Conclusion: This research contributes to the study of the genus, it is the first report of the chemical composition of B. sericea and demonstrates the importance of the dereplication process, allowing the identification of known compounds without time‐consuming procedures. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Antioxidant, anti‐glycation and anti‐inflammatory activities of methanol and ethyl acetate extracts of four Byrsonima species were evaluated and showed the potential of these plants. The presence of glycoside flavonoids, quinic acid derivatives, gallic acid derivatives, galloylquinic acids and proanthocyanidins was observed by HPLC‐DAD‐ESI‐MS/MS, in addition to two isomers of sinapic acid‐ O ‐hexoside described for the first time in the genus. This is the first report of the chemical composition of B. sericea and demonstrates the importance of the dereplication process.